Islamic project finance. Basic features - Kociemska, Hanna (Project finance w finansach islamskich. Podstawowe cechy, 2011)
The purpose of the article is to present the essence of Islamic project finance and the challenge against conventional project finance. The author introduces the basic rules of Islamic finance and the key instruments used in modern Islamic project finance structures. Islamic project finance’s value is demonstrated by the evidence of fast market development and the proper methods used to conduct key infrastructure investment. Even in spite of a strong financial crisis, there is an influence on the market
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 92-100
Keywords: project finance; Islamic finance; GCC countries; crisis; government revenue; Islamic project finance